2021
DOI: 10.1002/jclp.23104
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced psychological mindset intervention to promote adolescent wellbeing within educational settings: A feasibility randomized controlled trial

Abstract: Objective This randomized controlled trial feasibility study aimed to investigate a single‐session mindset intervention, incorporating third‐wave constructs, within educational settings as a universal tool to promote emotional wellbeing. Method Eighty adolescents (age M = 16.63) were randomized to the 30‐min computer intervention or a usual curriculum waitlist. Outcome measures were administered at baseline, posttreatment, 4‐week, and 8‐week follow‐ups. Results Student feedback about the intervention and trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Taken together, our findings underscore the value of growth mindset interventions among Asian schoolteachers. Past research shows that the growth mindset can be learned (Bettinger et al, 2018; Perkins et al, 2021; Rege et al, 2020; Yeager et al, 2019). A recent intervention study showed that a 30-min computerized growth mindset intervention can effectively enhance adolescents’ resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our findings underscore the value of growth mindset interventions among Asian schoolteachers. Past research shows that the growth mindset can be learned (Bettinger et al, 2018; Perkins et al, 2021; Rege et al, 2020; Yeager et al, 2019). A recent intervention study showed that a 30-min computerized growth mindset intervention can effectively enhance adolescents’ resilience.…”
Section: Discussionmentioning
confidence: 99%
“…A recent intervention study showed that a 30-min computerized growth mindset intervention can effectively enhance adolescents’ resilience. Compared to those in the waitlist group, adolescents who had received a growth mindset intervention showed higher self-compassion, more positive mood, and lower anxiety (Perkins et al, 2021). In addition, students who learned that the brain can be trained to become smarter when people work hard to learn new things preferred working on challenging math tasks and were more likely to enroll in advanced math courses afterwards (Bettinger et al, 2018; Rege, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Just over half of the programs that produced significant, positive results used Cognitive Behavioral Therapy (CBT) as the foundation for the content delivered, while just under half of the ineffective programs were based on the same psychological theory. Trials of programs driven by alternatives to CBT were much fewer in number and produced similarly mixed results; significant, positive effects were found in programs guided by Rational Emotive Behavior Therapy (David et al, 2019), Positive Psychology (Shoshani & Steinmetz, 2014;Shoshani et al, 2016) and education of growth mindsets and neuroplasticity (Miu & Yeager, 2014;Perkins et al, 2021). Additionally, programs based on ACT and mindfulness produced positive but non-significant effects (Burckhardt et al, 2017;Volanen et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…They conducted a follow-up measurement nine months later and found that the effects persisted (d = .29∼.60) for both parent-and self-reported levels of depression and anxiety (see also Schleider et al, 2019;Schleider & Weisz, 2018). Similarly, Perkins et al (2021) found that, among a group of students from the United Kingdom, a half-hour intervention program was enough to trigger positive changes in self-compassion, anxiety, and depression measurable in an eight-week follow-up.…”
mentioning
confidence: 97%
“…Having first made its way into psychological science in the 1970s, growth mindset, sometimes termed incremental (as opposed to entity) implicit theory, has received much attention in the last few decades (Yeager & Dweck, 2020). Generally defined as a belief that general or specific (e.g., intelligence, personality, socio-economic status) human attributes are malleable and could be improved over time, high levels of growth mindset have been proven predictive of several desirable outcomes, such as better academic and occupational performance (Caniëls et al, 2018; Costa & Faria, 2018; Han & Stieha, 2020), better mental health conditions (Burnette et al, 2020; Schleider et al, 2015; Tamir et al, 2007), and higher levels of well-being (Ortiz Alvarado et al, 2019; Perkins et al, 2021; Zhao et al, 2021).…”
mentioning
confidence: 99%